The Emergence of Social Gospel Radicalism: The Methodist Case - King, William McGuire (1981)
What happened to the social gospel impulse after World War I? Recent historians have demonstrated that many reformers did not bid farewell to reform in the 1920s.1 In the case of Protestant social liberalism, however, the precise relationship between postwar social action and the prewar social gospel movement requires further clarification. Was the former merely a continuation of the latter? Such a question is currently difficult to answer since few major studies of the social gospel bridge both historical periods. Indeed, the death or retirement by 1918 of so many early leaders of the social gospel movement, particularly Washington Gladden, Josiah Strong, and Walter Rauschenbusch, leaves the impression that an era had come to a close.